Metabolic associated fatty liver disease increases risk of adverse events after acute coronary syndrome. (3rd October 2022) - Chew, N; Ng, C H; Kong, G; Chin, Y H; Lim, O; Lim, W H; Dalakoti, M; Khoo, C M; Kong, W; Poh, K K; Foo, R; Lee, C H; et al.
Abstract:  : Metabolic Associated Fatty Liver Disease (MAFLD) was recently introduced as an alternative definition for fatty liver, that has been linked to an increased risk of systemic end-organ damage. However, current studies have not examined the impact of MAFLD on patients presenting with acute coronary syndrome (ACS). Here, we present a retrospective analysis on the short and long-term outcomes of ACS patients with MAFLD. Methods: A retrospective analysis was conducted in a tertiary care centre. Hepatic steatosis and fibrosis was examined with hepatic steatosis index and fibrosis-4 (FIB-4) index. The primary and secondary outcomes of the analysis were long term all-cause mortality, and in-hospital all-cause mortality, stroke, heart failure and cardiogenic shock respectively. Adjusted analysis was conducted for primary and secondary outcomes with covariates including age, sex, race, type of ACS and previous myocardial infarction. Results: A total of 5770 patients were included in the analysis, and 21% of ACS patients had concomitant MAFLD. MAFLD resulted in a 23% increase in long-term all-cause mortality compared to non-MAFLD (HR: 1.230, CI: 1.065 to 1.420, p=0.005). MAFLD increased the risk of in-hospital mortality, stroke, heart failure and cardiogenic shock compared to non-MAFLD. A sensitivity analysis conducted based on MAFLD with advance fibrosis, chronic kidney disease and diabetes also demonstrated significantly increased effect size magnitude of all-cause mortality, compared to non-MAFLD. Conclusion: MAFLD represents an encapsulation of metabolism dysregulation and has been associated with increased risk of systematic disease. The present study shows that MAFLD is associated with significantly increased adverse prognostic outcomes after ACS compared to non-MAFLD. An increase in awareness of MAFLD is required beyond the field of hepatology for improvements in multidisciplinary care and management. Funding Acknowledgement: Type of funding sources: None.